2011
DOI: 10.2134/agronj2010.0345
|View full text |Cite
|
Sign up to set email alerts
|

Combining Ability of Early‐maturing White Maize Inbreds under Stress and Nonstress Environments

Abstract: Maize (Zea mays L.) hybrids resistant to Striga hermonthica (Del) Benth and tolerant to drought are vital to the sustainability of productivity of the maize‐based farming systems of West and Central Africa (WCA). Thirty‐six diallel crosses derived from nine early maturing white maize inbreds were evaluated under drought, well‐watered, striga‐infested, and striga‐free conditions at five locations in Nigeria between 2007 and 2009. The objective was to examine the combining ability, performance and stability of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
58
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(86 citation statements)
references
References 33 publications
26
58
2
Order By: Relevance
“…These results are consistent with the findings of Badu-Apraku et al (2011) and. The presence of significant E × Cultivar and E × Era mean squares for grain yield and most measured traits under multiple stress and non-stress environments indicated differential responses of the genotypes and the need to identify high-yielding and stable cultivars across environments, as reported by Sabaghnia et al (2008); Moghaddam and Pourdad, (2009).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…These results are consistent with the findings of Badu-Apraku et al (2011) and. The presence of significant E × Cultivar and E × Era mean squares for grain yield and most measured traits under multiple stress and non-stress environments indicated differential responses of the genotypes and the need to identify high-yielding and stable cultivars across environments, as reported by Sabaghnia et al (2008); Moghaddam and Pourdad, (2009).…”
Section: Discussionsupporting
confidence: 89%
“…The presence of significant E × Cultivar and E × Era mean squares for grain yield and most measured traits under multiple stress and non-stress environments indicated differential responses of the genotypes and the need to identify high-yielding and stable cultivars across environments, as reported by Sabaghnia et al (2008); Moghaddam and Pourdad, (2009). This result confirmed the need for extensive testing of cultivars in multiple environments, including location and years before cultivar recommendations are made in the subregion (Badu-Apraku et al, 2011, 2015b.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…The score of leaf senescence (Leaf S) was recorded on the scale from 1 to 10 by dividing the percentage of estimated total dead leaf area by 10 (Bänziger et al, 2000) as 1 = 0-10% dead leaf, 2 = 10-20% dead leaf, 3 = 20-30% dead leaf, 4 = 30-40% dead leaf, 5 = 40-50% dead leaf, 6 = 50-60% dead leaf, 7 = 60-70% dead leaf, 8 = 70-80% dead leaf, 9 = 80-90% dead leaf and 10 = 90-100% dead leaf. Plant height (PHT) and ear height (EHT) were measured from the base of the maize plant to the top of the largest leaf and ear leaf, respectively using measuring tape (cm) (Badu-Apraku et al, 2012). Ears per plant (EPP) was recorded as the total number of ears which developed at least one full grain and divided by the total number of all the plants harvested in the plot (Bänziger et al, 2000).…”
Section: Data Collectionmentioning
confidence: 99%
“…This result agrees with those of Vivek et al (2010), Gichuru et al (2011) and Mutengwa et al (2012) who found out that additive gene effects were predominant in the inheritance of resistance to MSVD. High GCA mean square implied that the per se performance of the inbred lines used in this study should be a suitable pointer of the performance of their hybrids (Gethi and Smith, 2004;Badu-Apraku et al, 2011). For grain yield, the ratios for all were less than unity indicating that non-additive effect was more predominant, indicating that heterosis could be exploited from crossing the set of parental lines used in the study.…”
Section: Analysis Of Variance For Msvd Severity Mean Score and Grain mentioning
confidence: 91%